Checking Out the Future: A Perspective from African Theological Education. (July 2016) - Kaunda, Chammah J.
Abstract: This article refers to the Global Survey on Theological Education, conducted between 2011 and 2013, to provide sub‐Saharan African critical reflection on the future of theological education in the continent. It considers the many contextual factors and shifting world views shaping Africa today, including the demographic shift of the heartlands of Christianity from the North to the South. It summarizes and analyzes seven critical responses from the survey findings, concluding that issues such as accreditation, accountability, integrity of leaders, viability of vision, and collaboration must be perceived in their interdependence and addressed systematically and comprehensively for the future of theological education in African Christianity.1